A crane among wolves ebook - Hur, June (2024)
AN INSTANT NEW YORK TIMES BESTSELLER! AN EDGAR AWARD NOMINEE June Hur, bestselling author of The Red Palace , crafts a devastating and pulse-pounding tale that will feel all-too-relevant in today's world, based on a true story from Korean history. Hope is dangerous. Love is deadly. 1506, Joseon. The people suffer under the cruel reign of the tyrant King Yeonsan, powerless to stop him from commandeering their land for his recreational use, banning and burning books, and kidnapping and horrifically abusing women and girls as his personal playthings. Seventeen-year-old Iseul has lived a sheltered, privileged life despite the kingdom's turmoil. When her older sister, Suyeon, becomes the king's latest prey, Iseul leaves the relative safety of her village, traveling through forbidden territory to reach the capital in hopes of stealing her sister back. But she soon discovers the king's power is absolute, and to challenge his rule is to court certain death. Prince Daehyun has lived his whole life in the terrifying shadow of his despicable half-brother, the king. Forced to watch King Yeonsan flaunt his predation through executions and rampant abuse of the common folk, Daehyun aches to find a way to dethrone his half-brother once and for all. When staging a coup, failure is fatal, and he'll need help to pull it off—but there's no way to know who he can trust. When Iseul's and Daehyun's fates collide, their contempt for each other is transcended only by their mutual hate for the king. Armed with Iseul's family connections and Daehyun's royal access, they reluctantly join forces to launch the riskiest gamble the kingdom has ever seen: Save her sister. Free the people. Destroy a tyrant. Also by June Hur: The Silence of Bones The Forest of Stolen Girls The Red Palace